The Relationship Between Dietary Adherence and Random Blood Glucose Levels in Type 2 Diabetes Mellitus Patients at Malinau Regional General Hospital, North Kalimantan - Serfina Serfina; Resti Kusumarini Samben; Maurizka Pitria Putranti (Journal of Community Nutrition Intervention, 2026)
Type 2 diabetes mellitus (T2DM) is a significant chronic disease characterized by insulin resistance and impaired insulin secretion. It is a leading cause of microvascular and macrovascular complications, including blindness, kidney failure, and cardiovascular disease. Records from Malinau Regional General Hospital in North Kalimantan documented 2,300 cases, a 23% increase from 2022 to 2024. One key strategy in T2DM management is dietary intervention, which plays a critical role in maintaining stable blood glucose levels. This study aimed to analyze the relationship between dietary adherence and random blood glucose levels among patients with T2DM at Malinau Regional General Hospital. An analytical cross-sectional survey design was employed, involving 34 outpatients with T2DM selected by convenience sampling. As accidental sampling is a form of convenience sampling, it inherently introduces selection bias, which serves as a limitation of this study. Dietary adherence was assessed using a questionnaire based on the MMAS-8 and the 2021 PERKENI guidelines. Random blood glucose levels were categorized as normal (< 200 mg/dL) or high (\ge 200 mg/dL). The results showed that patients who adhered to dietary recommendations were more likely to have normal random blood glucose levels (p < 0.001), indicating a significant association between dietary adherence and glycemic control.